2005
DOI: 10.1002/hup.712
|View full text |Cite|
|
Sign up to set email alerts
|

Seasonal variations in [3H]citalopram platelet binding between healthy controls and violent offenders in Finland

Abstract: Monthly binding densities (B(max)) of [3H]citalopram to the platelet serotonin transporter (SERT) was measured longitudinally over 1 year in a control group of 18 healthy Finnish male volunteers. Single platelet samples were also analysed from 33 men who were incarcerated for violent crimes during the same calendar year. A statistically significant seasonal variation in SERT B(max) was observed in both data sets, and bi-monthly floating averages for SERT B(max) were calculated and then fit to an annual sinusoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Platelet levels of 5‐HTT exhibit seasonal variations (29). Furthermore, genetic polymorphisms in the promoter as well as in intron regions of the 5‐HTT gene render the individuals involved more prone to stress and depression (30,31).…”
Section: Release and Reuptake Of 5‐htmentioning
confidence: 99%
“…Platelet levels of 5‐HTT exhibit seasonal variations (29). Furthermore, genetic polymorphisms in the promoter as well as in intron regions of the 5‐HTT gene render the individuals involved more prone to stress and depression (30,31).…”
Section: Release and Reuptake Of 5‐htmentioning
confidence: 99%
“…A number of studies showed seasonal changes in serotonergic parameters, including brain serotonin concentration and turnover [34][35][36][37][38] . Furthermore, serotonin-related behaviours change with the seasons in clinical and non-clinical populations [34,[39][40][41][42][43][44][45][46][47] . The most important physiological mechanism controlling synaptic serotonin levels is reuptake of serotonin into the presynaptic neuron via the serotonin transporter (5-HTT) [48,49] .…”
Section: Serotoninmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Seasonal variations in peripheral serotonergic markers have been demonstrated in several studies. [12][13][14] A postmortem study 15 shows seasonal differences in serotonin concentration in the human hypothalamus; another study 16 suggests that sunlight alters serotonin turnover in the human brain.…”
mentioning
confidence: 99%